1996
DOI: 10.1002/(sici)1098-2752(1996)17:7<358::aid-micr3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Fibula free flap phalloplasty: Modifications and recommendations

Abstract: Radial forearm flap phalloplasty should be regarded as the gold standard. The large forearm donor site scar, however, has led to the search for other donor areas. We present our modifications and recommendations for addressing the ideal goals of phalloplasty better when applying the fibula free flap. We recommend preconstruction and secondary anastomosis of the neo-urethra. Preoperative infiltration of the cutaneous nerve is recommended for planning of the sensate flap. The osseous part of the flap should be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…For this, a radial forearm free flap (n ϭ 9), 2 an upper arm free flap (n ϭ 1), 12 an osteocutaneous fibula free flap (n ϭ 1), 13 or an extended iliac pedicled flap (n ϭ 1) has been used. 14 As 5 additional patients were scheduled for additional phalloplasty, a total of 17 out of our 70 patients (0.24) requested more comprehensive phalloplasty after having undergone metaidoioplasty.…”
Section: Postmetaidoioplasty Phalloplastymentioning
confidence: 99%
“…For this, a radial forearm free flap (n ϭ 9), 2 an upper arm free flap (n ϭ 1), 12 an osteocutaneous fibula free flap (n ϭ 1), 13 or an extended iliac pedicled flap (n ϭ 1) has been used. 14 As 5 additional patients were scheduled for additional phalloplasty, a total of 17 out of our 70 patients (0.24) requested more comprehensive phalloplasty after having undergone metaidoioplasty.…”
Section: Postmetaidoioplasty Phalloplastymentioning
confidence: 99%
“…5) (Papadopulos et al, 2008). The proximal end of the fibula is fixed to the periosteum of the pubic symphysis using sutures and tiny burr holes (Sadove et al, 1993;Papadopulos et al, 2008;Hage et al, 1996).…”
Section: The Surgical Techniquementioning
confidence: 99%
“…11). 19,20 Sadove et al found that prelamination of the neo-urethra reduced the incidence of urethral fistulas 21 and better controlled girth because the flap is wrapped around the urethra rather than tubed. For prelamination of the neo-urethra a full thickness skin graft wrapped around a catheter is inserted into the leg.…”
Section: Myocutaneous Latissimus Dorsi Flapmentioning
confidence: 99%
“…Hage et al recommend preoperative sensory marking by injecting lidocaine over the biceps femoris tendon and marking the resulting numb area on the lateral aspect of the lower leg. 20 The bone is then fixed to the penile corpora cavernosa or the pubic symphysis. Hage et al suggest making the bone $2 cm longer than the skin paddle so that the phallus is not floppy.…”
Section: Myocutaneous Latissimus Dorsi Flapmentioning
confidence: 99%